CometCIEF: A web-based image enhancement facility to digitally enhance images of cometary comae. (1st December 2015) - Martin, M. Patrick; Samarasinha, Nalin; Larson, Stephen
Abstract: We present details of an online web facility for enhancing coma images of comets. This facility, the Cometary Coma Image Enhancement Facility (CometCIEF), allows a user to enhance FITS images using five advanced image enhancement techniques which were not previously available as an open source. The resultant enhanced image as well as intermediate images produced during the enhancement process can then be downloaded as FITS images. We provide additional documentation and source codes for the user to download at the Facility, available athttp://www.psi.edu/research/cometimen .